Transformacja systemu rządów w Turcji po nowelizacji Konstytucji z 2017 r. .......... 53 - Kozanecki, Karol (Współczesne zmiany konstytucji w wybranych państwach europejskich: Pomiędzy partykularyzmem prawnym a wspólnotą doświadczeń, 2025)
TRANSFORMATION OF THE SYSTEM OF GOVERNMENT IN TURKEY AFTER THE AMENDMENT OF THE CONSTITUTION IN 2017This article provides an analysis of Turkey’s systemic transformation, culminating in the 2017 constitutional amendment. The author argues that, beyond a mere strengthening of the executive, this reform led to the erosion of the separation of powers and the formation of a super-presidential system. A key element of this transformation was the shift from a dualistic to a monocratic executive, concentrated solely in the hands of the president following the abolition of the office of the prime minister and the Council of Ministers. The analysis shows that the head of state’s position was to bypass the parliament, as well as through the subordination of the judiciary. This was achieved by gaining decisive influence over the appointments to key bodies such as the Constitutional Court and the Council of Judges and Prosecutors. Simultaneously, the role of the parliament was weakened, notably by granting the president the arbitrary right to dissolve it and by abolishing the mechanism of the government’s parliamentary accountability. In conclusion, the author asserts that the Turkish model, due to its extreme concentration of power and the dismantling of checks and balances, can be perceived as a super-presidential system akin to the Russian model. These changes are analyzed as an expression of legal particularism while also fitting into a broader specific “community of experiences” among states facing a crisis of the rule of law.